An Analysis of English Teachers’ Difficulties and Strategies in Implementing Merdeka Curriculum on the Seventh Grade at SMPN 1 Panyabungan Selatan - Syahrida Awaliyah; Yuli Tiarina (Universitas Negeri Padang, 2023)
This research aimed to find out the difficulties faced by English teachers in Implementing Merdeka curriculum on the seventh grade at SMPN 1 Panyabungan Selatan. The researcher also analyzed the strategies used by the teachers to overcome those difficulties. To obtain the results, researcher used interview as the instrument, while the method used on this research was descriptive qualitative. As the informants, researcher chosen three first grade English teachers at SMPN 1 Panyabungan Selatan. The results of this research indicated that there were five difficulties faced by English teachers in implementing Merdeka curriculum.Those five difficulties were understanding new terms found in Merdeka curriculum (learning outcomes (CP), learning objectives (TP), the flow of learning objectives (ATP)), giving assessment (the different focus of assessing made teacher difficult to do an assessment), choosing learning styles (because the learning centre was different from the previous curriculum), unsupported library (there were no books that teachers needed related Merdeka curriculum implementation in the library), unsupported IT network (teachers were not able to access Merdeka teaching platform because of unsupported network). To overcome those difficulties, teachers used four strategies. The four strategies meant were joining webinar, looking for E-books, utilizing application on gadget (youtube and tiktok), and left the school to find supported network (if the teachers wanted to access Merdeka teaching platform). The findings of this research expected to give benefits for English teachers, especially to overcome the difficulties faced in implementing Merdeka curriculum.